A new equation to predict the total potential longshore sediment transport rate in the beach ocean area. (2018) - Khorram, Saeed; Vahedi, Mahede
This paper proposes a novel predictive formula for the estimation of the total longshore sediment transport rate (TLSTR) using the incomplete selfsimilarity (ISS) and sediment transport physics principles with the assumption that sediments are mobilised by breaking waves. The key factor in this study is the use of dimensional analysis and self-similarity concepts based on a number of independent variables to develop an integrated classical formula for the noncohesive TLSTR in marine coastal regions. To assess the prediction capability of the proposed formula, high-quality sediment transport and hydrodynamics datasets were gathered and six well-known formulae were employed for both the field and laboratory test conditions. Results show that the novel formula agrees well with both the flume and field data and it is quite suitable both for practical applications in coastal regions and for the numerical modelling of sediment transport and nearshore variations.